Optimism, pain coping strategies and pain intensity among women with rheumatoid arthritis - Zuzanna Kwissa-Gajewska; Marzena Olesińska; Anna Tomkiewicz (Rheumatology, 2014)
Objectives: According to the biopsychosocial model of pain, it is a multidimensional phenomenon, which comprises physiological (sensation-related factors), psychological (affective) and social (socio-economic status, social support) factors. Researchers have mainly focused on phenomena increasing the pain sensation; very few studies have examined psychological factors preventing pain. The aim of the research is to assess chronic pain intensity as determined by level of optimism, and to identify pain coping strategies in women with rheumatoid arthritis (RA). Material and methods : A survey was carried out among 54 women during a 7-day period of hospitalisation. The following questionnaires were used: LOT-R (optimism; Scheier, Carver and Bridges), the Coping Strategies Questionnaire (CSQ; Rosenstiel and Keefe) and the 10-point visual-analogue pain scale (VAS). Results: The research findings indicate the significance of optimism in the experience of chronic pain, and in the pain coping strategies. Optimists felt a significantly lower level of pain than pessimists. Patients with positive outcome expectancies (optimists) experienced less pain thanks to replacing catastrophizing (negative concentration on pain) with an increased activity level. Regardless of personality traits, active coping strategies (e.g. ignoring pain sensations, coping self-statements – appraising pain as a challenge, a belief in one’s ability to manage pain) resulted in a decrease in pain, whilst catastrophizing contributed to its intensification. The most common coping strategies included praying and hoping. Employment was an important demographic variable: the unemployed experienced less pain than those who worked. Conclusions : The research results indicate that optimism and pain coping strategies should be taken into account in clinical practice. Particular attention should be given to those who have negative outcome expectations, which in turn determine strong chronic pain regardless of coping strategies. Intensification of positive outcome expectations and seeking benefits in the RA experience could therefore constitute effective techniques in the clinical therapy process.